Miscellaneous New Species of Brazilian Bromeliaceae – III - Leme, Elton M. C.; Till, Walter; Kollmann, Ludovic J.c.; Moura, Ricardo L. De; Ribeiro, Otavio B.c. (Phytotaxa, 2014)
The authors describe and illustrate 14 new Bromeliaceae species: Aechmea avaldoana, Ae. gregaria, Ae. timida, Alcantarea lanceopetala, A. nana, A. recurvifolia, Billbergia matogrossensis, Bromelia amplifolia, Cryptanthus walkerianus, Encholirium viridicentrum, Vriesea bifida, V. lilliputiana, V. magnibracteata and V. tubipetala.